Facile synthesis of starch-maleate monoesters from native sago starch - Soon, Hiang Tay; Suh, Cem Pang; Suk, Fun Chin (Elsevier, 2012)
This paper documented a facile and green approach for synthesizing water soluble cross-linked starch-maleate monoester gel particles from native sago starch (Metroxylon sagu). Starch-maleate (SM) monoester gel was initially synthesized by reacting sago starch with maleic anhydride in an aqueous medium, and followed by precipitating in absolute ethanol. The transformation of starch-maleate gel into cross-linked gel particles of mean diameter 445 ± 115 nm occurred upon UV irradiation in the presence of cerium(IV) ammonium nitrate. The substitution of maleic anhydride onto starch chains was confirmed by FTIR spectroscopy, and the degree of substitution (DS) as determined by the back-titration method was within the range of 0.03–0.21. The water absorbency and hydrophilicity of SM samples of DS < 0.03 was substantially lower than SM samples of DS > 0.08. Being non-toxic, biocompatible and cheap, the potential utility of starch-maleate gel particles as drug delivery carriers in biomedical applications is therefore envisaged.